Amalan Senaman dan Kandungan Kolesterol - Syed Kamaruzaman Ali; Umi Farihah (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2013)
Everyone needs cholesterol. But, make sure the level of cholesterol in our body is not too high. If the cholesterol level is too high, may be our body will facing a few of diseases such as coronarie heart disease, hypertention, stroke, aterosclerosis, etc. Related to this issue, this article will elaborate some aspect related to the risk of high level of cholesterol, the factors that causes the high cholesterol, the exercise effect on the cholesterol level and the related theories. Based on this theories hopefully we will aware about the important of doing exercises to decrease cholesterol level